THE UNIQUE CASE OF JULIUS STREICHER : THE FIRST INTERNATIONAL TRIAL IN HISTORY FOR HATE SPEECH - Gujaničić, Dušan (Political Review, 2023)
The trial on the International Military Tribunal after World War II represents undoubtedly a touchstone both in legal history and in the history of civilization in general. Among 24 defendants selected in the different kinds of Nazi officials, the case of Julius Streicher is very specific. The main feature of his case is the fact that he was the unique Nazi official who was indicted and convicted “only” because of his hate speech towards the Jewish people, representing thus perhaps one of the most visible personifications of the Nazi regime. The intensity of his hate speech did not know any limit to the extent that he openly and brutally compared in his own newspapers all the Jews with some kind of animals or, even worse, with some contagious illnesses, and moreover, did it tirelessly for more than twenty years within everyday awful campaign addressed to the entire German people. During the trial, it was undeniably proved that Streicher knew about the mass murders of Jews, especially in the east of Europe, which was considered by the trial chamber as an aggravating circumstance. Among all those novelties introduced by the Nuremberg trial, we can see the crime against humanity as a new international crime since 1945, which was the subject of complaints of defendants’ attorneys claiming rightly from the legal point of view that the newly created crime violates one fundamental principle of modern criminal law – the principle of legality. On the other hand, besides this procedural dimension of the Nuremberg trial, the key question remained substantially unresolved: did Streicher’s hideous everyday campaign against Jews effectively influence the mass murder of Jews? Nonetheless, the potential answer suggests to us that the case of Julius Streicher will certainly remain a good example for all future analyses of judicial treatment of hate speech, but also for future contributions and developments of international criminal law.